Faktor yang Mempengaruhi Minat Pembelian Ulang di Kedai Kopi Wajik Coffee Kudus - hasan, fuad; Annan Awang Ghiffari (Fakultas Ekonomi Universitas Kadiri, 2024)
The increasing number of coffee shops has an impact on the level of competition between coffee shops in attracting new consumers and retaining old consumers to make repurchases. One of the coffee shops that is still struggling to compete, even though the number of consumers coming in fluctuates, is Kedai Wajik Coffee Kudus. This research aims to determine the level of repurchase intention and the factors that influence consumer purchasing decisions at Kedai Wajik Coffee Kudus. Primary data was collected using a questionnaire with a sample size of 43 consumers. Data were analyzed using descriptive analysis and multiple linear regression with the independent variables were price and service quality. The results of descriptive analysis showed that consumers at Wajik Coffee Kudus have good perceptions of price, service quality and repurchases. The regression results showed that the factor that has a significant influence on repurchases intention was service quality